The Moral Responsibilities of Companies - Chapple, C. author. aut Link
VII, 243 p.
Keywords: The Moral Responsibilities of Companies is a philosophical analysis of the question of whether companies can be held morally responsible for the harms they create, and what implications such a view has on the moral position of employees and shareholders in these companies.